Diffusion and Invisibility of French-speaking researchers.Afterword - (:unkn) unknown (My University, 2024)
Julia Ndibnu-Messina Ethé and a group of researchers from the ACETELACH Researchers Association offer us the results of their survey on the dissemination of research by French-speaking African academics in the field of literature and languages
Keywords: African Research